Research on the Current Status of Power Battery Recycling for New Energy Vehicles - Zhang, Menglu (International Journal of Global Economics and Management, 2025)
The rapid growth of China's new energy vehicle industry has led to a surge in decommissioned power batteries, making their recycling crucial for environmental protection and resource sustainability. This study examines China's power battery recycling status, identifying three main models and key challenges: inconsistent standards, unregulated channels, and inadequate infrastructure, which hinder efficiency and increase environmental risks. Proposed solutions include establishing unified standards, enhancing regulations and incentives, and optimizing a three-tier recycling network. These measures aim to improve recycling efficiency and support China's "double carbon" goals and circular economy development.